The Institutionalisation of Evaluation in Asia-Pacific
XVI, 593 p. 29 illus., 24 illus. in color.
Keywords: This book examines the progress of institutionalisation of evaluation in Asia Pacific from various perspectives. It presents prior developments and current states of evaluation in 11 countries, focusing on three dimensions, namely the political, social and professional systems. These detailed country reports, which have been written by selected researchers and authors of the respective countries, lead to a concluding comparison and synthesis. In addition, the influence of transnational organizations on the institutionalisation of evaluation is examined. This is the third of four volumes of the compendium The Institutionalisation of Evaluation. The first volume on Europe was published in 2020, and the second volume on the Americas in 2022. It will be followed by another volume on Africa. The overall aim is to provide an interdisciplinary audience cross-country learning to enable them to better understand the institutionalisation of evaluation in different nations, world regions and sectors. Reinhard Stockmann is Professor of Sociology at Saarland University, Germany. He is Founder and Director of the Center for Evaluation (CEval). Wolfgang Meyer is Professor of Sociology at Saarland University, Germany and Adjunct Professor at Uganda Technology and Management University, Kampala, Uganda. Niklas Zierke is a Research Associate at Saarland University, Germany. .